Effects of Early-Life Adversity on Tooth Enamel Formation - Shaffer, Ida C.; Nakano, Yukiko; Pham, Aidan; Short, Annabel; Nanci, Antonio; Zhang, Yan; Shemirani, Rozana; Den Besten, Pamela K. (Frontiers in Dental Medicine, 2022)
In a systemic effort to survive environmental stress, organ systems fluctuate and adapt to overcome external pressures. The evolutionary drive back towards homeostasis, makes it difficult to determine if an organism experienced a toxic exposure to stress, especially in early prenatal and neonatal periods of development. Previous studies indicate that primary human teeth may provide historical records of experiences related to stressors during that early time window. To assess the molecular effects of early life adversity on enamel formation, we used a limited bedding and nesting (LBN) mouse model of early life adversity (ELA) to assess changes in enamel organ gene expression and enamel matrix mineralization. On average, postnatal day 12 (P12) ELA mice weighed significantly less than controls. When adjusted for animal weight, ELA molar enamel volume was reduced as compared to controls, and relative mineral density of molar enamel was significantly increased. There were no obvious changes in enamel matrix crystal morphology or structure in ELA as compared to control mouse enamel. RNAseq showed Extracellular Matrix Organization to be the most significantly affected GO and Reactome pathways, whereas Butanote Metabolism was the most significantly altered KEGG pathway. Transcripts expressing the enamel matrix proteins amelogenin (Amelx) and enamelin (Enam) were among the top 4 most differentially expressed genes. When evaluating molecular mechanisms for the changes in gene expression in ELA enamel organs, we found significantly increased expression of Dlx3, while transcripts for clock genes Per1 and Nrd1 were downregulated. These findings support the possibility that the developing enamel organ is sensitive to the pressures of early life adversity and produces molecular and structural biomarkers reflecting these challenges.